PENERAPAN TEKNIK MODELLING DAN LATIHAN UNTUK MENINGKATKAN KETERAMPILAN SENAM AEROBIK DAN SENAM LANTAI - Heri Siswanto (Journal of Physical Education Health and Sport, 2014)
The purpose of this study was to determine whether the application of modeling and exercises techniques to improve aerobics and floor exercise in gymnastics on 3 K - 1 SMK Negeri 1 Temanggung in the 2nd of academic year 2012/2013 . data collected by using test techniques to determine student learning outcomes and non- test techniques by using observation sheets to determine the learning process. The research method used was Classroom Action Research to perform two actions in two cycle . The results of this research note that there were improvement in learning outcomes and learning processes. The first cycle increase students performance in the average value of 74.77 to 78.83 (5.43 %). In second cycle, the average value is 85.26 which means an increase of 14.03 % from the initial conditions . Similarly, the learning process showed an increase in activity and creativity of students and teachers . It can be concluded that the application of modeling techniques and exercises to improve aerobics and floor exercise in gymnastics on 3 K - 1 SMK Negeri 1 Temanggung in the 2nd of academic year 2012/2013